Positivism and Postpositivism: A Paradigmatic Analysis of Science and Islamic Education in Indonesia - Sulhan Yus; Warul Walidin; Zohaib Hassan Sain (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: Positivism and Postpositivism: A Paradigmatic Analysis of Science and Islamic Education in IndonesiaObjective: This study aims to compare the positivism and postpositivism paradigms within the context of science and Islamic education in Indonesia. Methods: The research uses a qualitative-descriptive design, with a literature review as the primary data collection method. This research was conducted in 2024, and data were analyzed using three steps: (1) data reduction, (2) data display, and (3) data presentation. Results: Islamic education in Indonesia predominantly uses a positivistic approach which emphasize scientific methods and objectivity in learning process. Conclusion: Islamic education in Indonesia needs to develop an integration between the two paradigms (positivism and post-positivism) by balancing objective scientific methods with more humanistic and transcendental perspectives. Contribution: This research contributes curriculum development in Islamic education. Positivism informs the formulation of curriculum grounded in factual and testable research results, while postpositivism ensures that the curriculum is relevant to students' social and cultural contexts.INDONESIAN: Positivisme dan Postpositivisme: Suatu Analisis Paradigma Ilmu dan Pendidikan Islam di IndonesiaTujuan: Penelitian ini bertujuan untuk menganalisis perbandingan antara paradigma positivisme dan postpositivisme dalam konteks ilmu pengetahuan dan pendidikan Islam di Indonesia. Metode: Desian penelitian menggunakan pendekatan kualitatif-deskriptif, dengan studi literatur sebagai instrumen utama. Penelitian ini dilaksanakan pada tahun 2024. Data dikumpulkan melalui telaah literatur (hasil penelitian). Analisis data dilakukan melalui (1) data reduction; (2) display data: (3) penyajian data: Hasil: Pendidikan Islam di Indonesia lebih dominan menggunakan pendekatan positivistik yang menekankan pada penggunaan metode ilmiah dan objektivitas dalam pembelajaran. Kesimpulan: pendidikan Islam di Indonesia perlu mengembangkan integrasi antara kedua paradigma tersebut (positivisme dan post-positivisme) dengan menyeimbangkan metode ilmiah yang objektif dan pendekatan yang lebih humanistik serta transendental. Kontribusi: Penelitian ini berkontribusi terhadap desain kurikulum pendidikan Islam. Positivisme berperan dalam merumuskan kurikulum yang berbasis pada fakta dan hasil riset yang dapat diuji, sementara postpositivisme mendorong agar kurikulum tersebut relevan dengan konteks sosial dan budaya siswa